English Correspondence: Case Study of English Education Department of University of HKBP Nommensen Students' Perspective of Cover Letter/Application Letter - Nababan, Irene Adryani; Sitanggang, Anita; Irwansyah, Syalaisha Syafira; Budiarti, Rika; Tobing, Viola Sasti Bizora L.; Sitanggang, Loria Vikki (Universitas Pahlawan Tuanku Tambusai, 2025)
This research investigates the perspectives of English Education Department students at the University of HKBP Nommensen regarding cover letter writing within the English Correspondence course. Recognizing the importance of cover letters in professional communication and career development, the study aims to assess students' understanding, challenges, and confidence in mastering this skill. Using a qualitative descriptive methodology, data were collected from 25 students through questionnaires and from 10 students through semi-structured interviews. Key findings reveal that while students acknowledge the relevance of cover letter writing to their future careers, they face challenges in organizing content, maintaining professionalism, and tailoring letters to specific job requirements. The research highlights the effectiveness of course materials but identifies a need for more interactive and practical teaching methods, such as workshops, peer reviews, and real-world applications. The findings offer actionable recommendations to enhance the teaching and learning process, ensuring students are better prepared for professional communication and the competitive job market.